An Analysis of John Smith’s Character in The Novel “I am Number Four” - Nopriansah1 Nopriansah1; Widya Astuti (Literary Criticism, 2018)
In I am Number Four novel by James Frey and Jobie Hughes, there is a main character named John Smith. He is 15 years old and at his age, he is in puberity phase which his characters are influenced by people around him. This research was conducted using psychosocial study. The purposes of this study are to analyze what the factors that influence John Smith’s characters and what the psychosocial problems that emerge in the development of John Smith’s character. The method used was qualitative descriptive method. Data were collected by using content analysis techniques. Based on the findings, that each character of John Smith is influenced by biological factor, familial factor and cultural and situational factor. The character of the biological factor is the genetic character that john smith gets from his grandfather. The character of the familial factor is a character that he imitates from Henri as his adoptive father. The last is the character of cultural and situational factor, this is a character that he gets through the interaction with the people around him and the situation he faces. The psychosocial problems that emerge in the development of John Smith’s character are the emotional problems that he feels, those are; fear, temprament and melancholic. Keywords: Psychosocial, Character, I Am Number Four Novel.